A study of disclosure practices and accountability of Malaysian zakat institutions - Raedah Sapingi (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2020)
The current study aims to investigate the accountability on the disclosure of zakat institutions (ZIs) through their annual reports. This study is motivated by the findings from previous studies regarding inadequate information disclosure by ZIs especially information on zakat disbursement as had been raised by the zakat payers (ZPs) and zakat recipients (ZRs). This has sparked public debates regarding the accountability and transparency of ZIs in disclosing zakat information, especially for public viewing. The issue further rose as there is an asymmetrical of information exists among the agency parties representing the ZIs i.e. the zakat managers (ZMs), ZPs, and ZRs as discussed in the past literature. As ZIs fall under the jurisdiction of the states, the current study believes that the issue emerged due to the inconsistencies of disclosure practices among the institutions. In light of this gap and limited studies regarding this area; the study intends to explore deeper disclosure practices in ZIs' annual reports by asking the opinions of agency parties and to propose a zakat disclosure index known as i-ZkDI. Additionally, the current study is also interested in identifying the expectations from panel of experts with respect to the adequacy of disclosure by ZIs. A sequential exploratory mixed-method approach and content analysis of ZIs' annual reports were employed. Findings from the interviews conform the existence of asymmetrical information among the agency parties. On the contrary, the ZMs opined that the reports prepared are sufficient although they acknowledged it needed improvements. In the second phase, through the Delphi technique, a total of 96 disclosure items with five categories were agreed and confirmed by the panel of experts. The financial information category emerged as the top-rated category with the highest mean score accorded by the panel members. In the final phase, the content analysis showed that the extent of the ZIs' disclosure is still insufficient. Therefore, it is evidenced that the ZIs' disclosure of zakat information via annual reports are still inadequate, hence suggesting the impairment of accountability. This study contributes to the body of knowledge on the accountability of religious institutions, specifically on ZIs' disclosure with annual reports. Further, it also enriched the knowledge on Accountability from an Islamic perspective and Agency theory in the context of zakat disclosure, in general. The study recommends the authority to establish a central body to govern the zakat affairs in the country, and form a standardised or common reporting practices among the states. It is hoped with these taken into consideration, it would entail better disclosure practices of zakat institutions in Malaysia.